Twice-exceptionality in the film “August Rush”: a reflection from a neuropsychological perspective (Research, Society and Development, 2020)
Cinematic art allows for the most diverse real-life scenarios. With this, the cinema has approached issues of neuropsychiatric clinic in several ways. In the film “August Rush”, the producers address the theme of Giftedness. Therefore, the aim of this study is to analyze the characteristic behaviors of this condition that are portrayed in the film through the neuropsychological perspective. In addition, behaviors within a possible double exception were analyzed. The method used for the analysis was based on the Charles Maguerez Arch Methodology. It was observed that some characteristics among Giftedness can be both confused and interrelated with Attention Deficit Hyperactivity Disorder, which makes the diagnosis of this comorbidity difficult, as already described in the literature. The study of film analysis made it possible to associate the character's behaviors with the literature on Giftedness.